2021
DOI: 10.1039/d1sc03268b
|View full text |Cite
|
Sign up to set email alerts
|

The Pd-catalysed asymmetric allylic alkylation reactions of sulfamidate imines

Abstract: The Pd-catalysed asymmetric allylic alkylation (Pd-AAA) of prochiral enamide anions derived from 5H-oxathiazole 2,2-dioxides has been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…[77] Other collaborative efforts have also uncovered a novel Rh I -catalyzed dehydro Diels-Alder reaction of enediynes 126 proceeding O via a rhodium-stabilized cyclic allene (Scheme 33c) [78] and the Pd-catalyzed asymmetric allylic alkylation reactions of sulfamidate imines. [79] In other studies on metal-promoted or metal-catalyzed cyclization reactions we have reported cyclization-cyanation and cyclization-halogenation reactions of β-hydroxyalkynes and o-alkynyl-anilines and phenols, leading to valuable 3-cyano-indoles and benzofurans, [80] and cycloisomerization reactions leading to furo[3,2-b]pyridines and furo [3,2-b]pyrroles. [81] Further studies on the PBMR resulted in the development of a highly diastereoselective synthesis of enantioenriched anti-α-allyl-β-fluoroamines from in situ prepared chiral α-fluoroaldehydes leading to 3-, 5-and 6-membered ring heterocycles, with the latter two types having an exo-cyclic alkylfluoro-substituent (Scheme 34a); [82] and the synthesis of enantioenriched anti-β-amino alcohols (Scheme 34b) via allylation reactions of in situ prepared chiral, O-protected α-hydroxyaldehydes.…”
Section: Other Developments On the Pbmrmentioning
confidence: 99%
“…[77] Other collaborative efforts have also uncovered a novel Rh I -catalyzed dehydro Diels-Alder reaction of enediynes 126 proceeding O via a rhodium-stabilized cyclic allene (Scheme 33c) [78] and the Pd-catalyzed asymmetric allylic alkylation reactions of sulfamidate imines. [79] In other studies on metal-promoted or metal-catalyzed cyclization reactions we have reported cyclization-cyanation and cyclization-halogenation reactions of β-hydroxyalkynes and o-alkynyl-anilines and phenols, leading to valuable 3-cyano-indoles and benzofurans, [80] and cycloisomerization reactions leading to furo[3,2-b]pyridines and furo [3,2-b]pyrroles. [81] Further studies on the PBMR resulted in the development of a highly diastereoselective synthesis of enantioenriched anti-α-allyl-β-fluoroamines from in situ prepared chiral α-fluoroaldehydes leading to 3-, 5-and 6-membered ring heterocycles, with the latter two types having an exo-cyclic alkylfluoro-substituent (Scheme 34a); [82] and the synthesis of enantioenriched anti-β-amino alcohols (Scheme 34b) via allylation reactions of in situ prepared chiral, O-protected α-hydroxyaldehydes.…”
Section: Other Developments On the Pbmrmentioning
confidence: 99%
“…13 Recently, a Pd-catalyzed asymmetric allylic alkylation of 4,5-disubstituted cyclic sulfamidate imines with allyl carbonates was reported by Pyne et al (Scheme 1b). 14 In the past decades, the Morita−Baylis−Hillman (MBH) carbonates have also been widely utilized as allylation agents for allylic alkylation reactions. 15 Typically, these reactions were promoted by nucleophilic catalysts such as tertiary amines or phosphines.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, Breinbauer et al described an efficient α-allylation of imine-containing heterocycles mediated by a Pd/Xantphos catalyst system, which proceeded without the addition of strong bases or Lewis acids (Scheme a) . Recently, a Pd-catalyzed asymmetric allylic alkylation of 4,5-disubstituted cyclic sulfamidate imines with allyl carbonates was reported by Pyne et al (Scheme b) …”
Section: Introductionmentioning
confidence: 99%
“…We therefore designed a new azadiene dipolarophile that would completely preclude (4 + n ) reactivity and enable reliable (3 + 2) processes with VCPs to be realised. From our experience with cyclic sulfamidate imines, 56 we envisaged that sulfamidate imine-derived azadienes (SDAs) would be an intriguing alternative to the BDA system that would completely preclude the (4 + n ) reaction mode and give highly functionalised cyclopentanes ( Fig. 2b ).…”
Section: Introductionmentioning
confidence: 99%